Why, when and where did honey bee dance communication evolve? - I'Anson Price, Robbie; Grüter, Christoph (Frontiers in Ecology and Evolution, 2015)
Honey bees (Apis sp.) are the only known bee genus that uses nest-based communication to provide nest-mates with information about the location of resources, the so-called “dance language.” Successful foragers perform waggle dances for high quality food sources and suitable nest-sites during swarming. However, since many species of social insects do not communicate the location of resources to their nest-mates, the question of why the dance language evolved is of ongoing interest. We review recent theoretical and empirical research into the ecological circumstances that make dance communication beneficial in present day environments. This research suggests that the “dance language” is most beneficial when food sources differ greatly in quality and are hard to find. The dances of extant honey bee species differ in important ways, and phylogenetic studies suggest an increase in dance complexity over time: species with the least complex dance were the first to appear and species with the most complex dance are the most derived. We review the fossil record of honey bees and speculate about the time and context (foraging vs. swarming) in which spatially referential dance communication might have evolved. We conclude that there are few certainties about when the “dance language” first appeared; dance communication could be older than 40 million years and, thus, predate the genus Apis, or it could be as recent as 20 million years when extant honey bee species diverged during the early Miocene. The most parsimonious scenario assumes it evolved in a sub-tropical to temperate climate, with patchy vegetation somewhere in Eurasia.